Correction and Validation of Daily Rainfall Satellite Data in the Wae Mese Watershed, Labuan Bajo, West Manggarai Regency - Yudarsi, Pankrasio Mario; Wicaksono, Albert; Wijaya, Obaja Triputera (International Journal of Science and Society, 2025)
This study aims to analyze rainfall correction in the Wae Mese watershed, located in Labuan Bajo, focusing on improving the accuracy of rainfall data for flood modelling and watershed management planning. In this research, corrections are performed using an objective function that compares observed rainfall data with satellite-based rainfall data from GPM (Global Precipitation Measurement). The objective function is used to evaluate prediction errors and determine the most effective correction factor to enhance the reliability of satellite rainfall data. The research methodology includes the application of the objective function to measure differences between satellite-derived rainfall data and observed data, and applying corrections based on the analysis results. The findings show that rainfall data corrected using the objective function provides a more accurate representation of rainfall events, leading to more precise flood predictions for the watershed. This study highlights the importance of using the objective function in rainfall correction, which plays a key role in effective flood risk management and planning. These findings provide a better understanding of rainfall patterns in the Wae Mese watershed and support the use of corrected satellite-based rainfall data for hydrological modelling and future flood risk assessments.